ADDITION OF VINEGAR TO EXTEND THE SHELF-LIFE OF CABEÇA DE XARA - Laranjo, Marta (2017)
Cabeça de xara is a ready-to-eat meat product, whose production is very characteristic in Alentejo, a particular region of Portugal. It is a galantine usually moulded into parallelepiped shape made with various meats obtained from the Alentejano pig breed reared in the same region, namely deboned pork heads, tongue and connective tissue to which a number of condiments like salt, parsley, wine and pepper, are added. This work intended to test the feasibility of adding vinegar in order to increase the shelf-life of cabeça de xara, by reducing the contaminating microbiota responsible for spoilage, as well as controlling the pathogen Listeria monocytogenes. Three independent batches were produced and proximate composition, pH, aw, microbiological parameters and biogenic amines content evaluated. A sensory analysis was also performed throughout the storage period. No significant differences between control and vinegar samples was found regarding the proximate composition of cabeça de xara. As expected, pH is lower in the vinegar samples, however no differences in aw were observed between the two treatments. L. monocytogenes was present from the first month on only in one batch in the control treatment. However, it is inhibited by the addition of vinegar until the third month of storage, where L. monocytogenes is present but below the limit established in the 2073/2005 regulation. The presence of vinegar significantly decreased the content in biogenic amines, particularly cadaverine, putrescine and tyramine, throughout the storage period. Concerning sensory evaluation, no vinegar taste was reported by the panellists in a depreciating way.